The association of prenatal exposure to particulate matter with infant growth: A birth cohort study in Beijing, China. (15th May 2021) - Zhou, Shuang; Lin, Lizi; Bao, Zheng; Meng, Tong; Wang, Shanshan; Chen, Gongbo; Li, Qin; Liu, Zheng; Bao, Heling; Han, Na; Wang, Haijun; Guo, Yuming
Abstract: Limited studies examined the associations of prenatal exposure to particulate matter (PM) and children's growth with inconsistent results, and no study focused on PM1 . We matched a birth cohort (10, 547 children) with daily PM1 and PM2.5 concentrations by maternal home addresses. Air pollution concentrations were predicted by satellite remote sensing data, meteorological factors, and land use information. The weight and length of children in the birth cohort were measured at approximately one year old. We calculated the Z-score of weight for length (WFL) and body mass index (BMI) and then defined overweight and obesity (OWOB) based on WHO Standards. Generalized linear regression and modified Poisson regression were used to identify the association of prenatal exposure to PM1 or PM2.5 with anthropometric measurements and risk of OWOB. We also determined the mediation effect of preterm birth on the associations. Results showed that a 10 μg/m 3 increase in prenatal exposure to PM1 and PM2.5 was significantly associated with a 0.105 [95% confidence interval (CI): 0.067, 0.144] and 0.063 (95% CI: 0.029, 0.097) increase in WFL Z-score for one-year-old children. Similar associations were found for BMI Z-score. A 10 μg/m 3 increase in prenatal PM1 and PM2.5 exposure was significantly associated with 1.012 (95% CI : 1.003, 1.021) and 1.010 (95% CI : 1.002, 1.018) times higher risk of OWOB. . Preterm birth mediated 7.5% [direct eﬀect (DE) = 0.106, P < 0.001; indirect eﬀect (IE) = 0.009, P < 0.001)] and 9.9% (DE = 0.064, P < 0.001; IE = 0.007, P < 0.001) of the association between prenatal PM1 and PM2.5 exposure and WFL Z-score of the children. The association of prenatal PM1 and PM2.5 exposure with BMI Z-score of children was also mediated by preterm birth by 6.6% (DE = 0.111, P < 0.001; IE = 0.008, P < 0.001) and 9.1% (DE = 0.064, P < 0.001; IE = 0.006, P < 0.001). These results remained robust in the sensitivity analyses. In conclusion, prenatal exposure to PM1 and PM2.5 increased WFL, BMI Z-scores and higher risk of OWOB for one-year-old children. The associations were partially mediated by preterm birth. These findings call for the urgent action on air pollution regulation to protect early-life health among children. Graphical abstract: Image 1 Highlights: We first studied the association of PM1 with the early onset of childhood obesity and the mediation effect of preterm birth. Prenatal exposure to PM1 and PM2.5 increased WFL, BMI Z-scores and risk of overweight and obesity for one-year-old children. The associations of prenatal PM exposure with WFL and BMI Z-scores of children were partially mediated by preterm birth.